Health economic analysis for the 'CURE Project' pilot: a hospital-based tobacco dependency treatment service in Greater Manchester. Issue 1 (22nd December 2021) - Evison, Matthew; Cox, Julian; Howle, Freya; Groom, Kathryn; Moore, Ryan; Clegg, Hannah; Pearse, Cheryl; Rutherford, Michael; Tempowski, Alex; Grundy, Seamus; Turnpenny, Beth; Law, Hou; et al.
Abstract : Introduction: Treating tobacco dependency in patients admitted to acute care National Health Service (NHS) trusts is a key priority in the NHS 10-year plan. This paper sets out the results of a health economic analysis for 'The CURE Project' pilot; a new hospital-based tobacco dependency service. Methods: A health economic analysis to understand the costs of the intervention (both for the inpatient service and postdischarge costs), the return on investment (ROI) and the cost per quality-adjusted life year (QALY) of the CURE Project pilot in Greater Manchester. ROI and cost per QALY were calculated using the European Study on Quantifying Utility of Investment in Protection from Tobacco and Greater Manchester Cost Benefit Analysis Tools. Results: The total intervention costs for the inpatient service in the 6-month CURE pilot were £96 224 with a cost per patient who smokes of £40.21. The estimated average cost per patient who was discharged on pharmacotherapy was £97.40. The cost per quit (22% quit rate for smokers at 12 weeks post discharge) was £475. The gross financial ROI ratio was £2.12 return per £1 invested with a payback period of 4 years. The cashable financial ROI ratio was £1.06 return per £1 invested with a payback period of 10 years. The public value ROI ratio was £30.49 per £1 invested. The cost per QALY for this programme was £487. Discussion: The CURE Project pilot has been shown to be exceptionally cost-effective with highly significant ROI in this health economic analysis. This supports the NHS priority to embed high-quality tobacco addiction treatment services in acute NHS trusts, and the CURE Project provides a blueprint and framework to achieve this.